Determinant Model of Tax Practice Adoption: Empirical Study on Umkm Assisted by Tax Center Gunadarma University - Ayu Amelia; Sudaryanto Sudaryanto (Dinasti Publisher, 2024)
In the era of modernization, MSMEs supported by the Gunadarma University Tax Center are increasingly adapting to digital marketing. To make it easier for MSMEs, Gundarma University created a mobile-based LaKu accounting application. This research was conducted to analyze the factors that influence interest in adopting the LaKu accounting application among MSMEs assisted by the Gunadarma Tax Center by applying the UTAUT model including performance expectations, business expectations, social factors and facilitating conditions. This research uses a saturated sampling technique by taking the entire population of 25 MSMEs assisted by the Gunadarma University Tax Center for research. The data source used is primary data from the results of distributing questionnaires. The method used is a quantitative method with multiple linear regression analysis. The results of this research indicate that Performance Expectations have a negative effect on LaKu Application Adoption. Business expectations and Social Factors do not influence LaKu Application Adoption. Meanwhile, Facilitating Conditions have a positive effect on LaKu Application Adoption. This is because MSMEs still experience difficulties when using the LaKu accounting application, so the application is less popular with them.